Effectiveness of Diorama Media on Grade III Students' Learning Outcomes in Metamorphosis Science Education - Pramudienda, Firstca Diin Febriarly; Sasomo, Budi; Ulfa Nur'Afifah, Uci (Papanda Publisher, 2025)
This research was carried out at SD Negeri Jururejo 2, Ngawi District, Ngawi Regency, with the aim of determining the effectiveness of the use of diorama media in improving the learning outcomes of grade III students on metamorphosis material in Natural and Social Sciences (IPAS) learning. The problem in this study departs from the initial findings which show that as many as 63.2% of students have not reached the Minimum Completeness Criteria (KKM) in metamorphosis material. This is because the material of metamorphosis is abstract and cannot be understood well through lecture methods or textbooks. Diorama media as a three-dimensional visual media is considered to be able to provide a concrete learning experience and in accordance with the characteristics of the cognitive development of elementary school students. This study uses a quantitative approach with a one-group pretest-posttest experimental design. The sample amounted to 19 grade III students, determined through saturated sampling techniques. The instrument is in the form of a multiple-choice test of 30 questions that have gone through validity and reliability tests. The results of the analysis showed an increase in the average score from 64.63 in the pretest to 93.26 in the posttest. The paired t-test produced a significance value (p < 0.05) and an effect size of 2.91 which showed a very large influence. It can be concluded that diorama media is effective in improving student learning outcomes in metamorphosis materials, creating more interesting, even, and easy learning for all students.